Penurunan Kualitas Telur Ayam Ras Petelur yang Disimpan pada Suhu Ruang di Kabupaten Tuban - Siswara, Hamzah Nata; Huda, Khoirul; Aini, Lia Nur (Jurnal Ilmu dan Industri Peternakan, 2023)
Eggs are one of the livestock product commodities that have good nutritional value and affordable prices, so they are quite popular. Storage of eggs among the consumer is still mostly done at room temperature. The storage process affects the decrease in egg quality, especially in areas with both high ambient temperatures and high humidity values too. The aim of this study was to determine the effect of storage time at room temperature in Tuban Regency on the quality of laying hen eggs. The study used a completely randomized design (CRD) with five treatments and four replications, and each replication consisted of 5 eggs. Each treatment contained 20 eggs, and the total eggs used were 100 eggs. After the egg storage process was complete, egg quality parameters were measured which included egg weight loss, egg air cell, albumen index (AI), yolk index (YI), haugh unit (HU), pH, and egg water content. The results showed that storage time had a significant effect (P<0.05) on all egg quality measurement parameters. The longer the eggs are stored, the egg weight loss, the AI, YI, HU and the water content of the eggs decreases. Meanwhile, the depth of the air cavity and the pH value of the eggs increased during storage at room temperature until the 20th day.